Evaluation of augmented reality and consumer perceptions in traditional diShes - Solmaz, Rıdvan; Pekersen, Yeliz (TAYLOR & FRANCIS INC, 2022)
The concept of augmented reality (AR) has made significant advances in the last two decades. This technology that is used in every field can also be used in preserving and archiving traditional dishes in a digital environment. Therefore, the purpose of this research is to develop an AR supported mobile application and to try to reveal how the application is perceived by making the consumers who eat at traditional restaurants experience the application. In the first phase, a mobile application was developed for this purpose. In the second phase, the qualitative research method was used and the mobile application was tested on 30 customers who eat in traditional restaurants and their reviews about the mobile application are considered. At the end of the study, most of the participants expressed that they liked the application and find it interesting and surprising to see 3d images inside the application.
Keywords: Augmented reality; user experience; technology adoption; traditional dishes; mobile application